Pendampingan Pembelajaran Matematika “Math Teaching” dengan Pendekatan Joyful Learning bagi Siswa Madrasah di Kepulauan Seribu - Dwirahayu, Gelar; Sobiruddin, Dindin; Fatra, Maifalinda; Satriawati, Gusni; Khairunnisa, Khairunnisa; Ardiansyah, Rangga; Hairani, Risa Cahya (ABDI MOESTOPO: Jurnal Pengabdian Pada Masyarakat, 2026)
Math teaching is one of the off-campus activities supporting the MBKM curriculum. This activity can strengthen undergraduate students' pedagogical, personal, and social competence. The community service was carried out in the Kepulauan Seribu district of DKI Jakarta Province using the Service Learning method. Service Learning means undergraduate students can apply their lecture knowledge at MI and MTs. The community service involved 70 undergraduate students and 12 lecturers. The results show that (1) Math teaching can be carried out effectively and efficiently, (2) undergraduate students can teach in MI and MTs well and provide a new atmosphere in the teaching process, they do not want to be taught by expository, they prefer by game methods or competition, (3) undergraduate students give a positive response to Math Teaching activities. This activity can improve their teaching skills, social care, and personal skills. In fact, according to the undergraduate students, some students from MI or MTs ask them to stay longer in the Kepulauan Seribu to teach more math. The recommendation is that community service activities must be carried out continuously either in the same area or in other areas because Indonesia's territory is very large.